STUDI KASUS PENGETAHUAN DAN SIKAP IBU PASCA PERSALINAN DENGAN PERAWATAN TRADISIONAL DI DESA JRAKAH KAB. PEMALANG TAHUN 2017 - Nur Aziz Setiadi; Djoko Nugroho; Ronny Aruben (Jurnal Kesehatan Masyarakat (Undip), 2017)
Traditional treatments using herbal and postnatal massage are still found in the area in Indonesia. Data from Riskesdas 2013 shows that 30.4% of households in Indonesia utilize traditional health services, 77.8% of households are traditional non-tool traditional health food and 49.0% of households use of herbs.18 The research objectives for knowledge and attitude analysis postpartum mother in Jrakah village Pemalang regency. This research is a mixed method research that is quantitative research with cross sectional design and to enrich the analysis result using qualitative FGD method with Posyandu cadre of Jrakah village. The result of the research shows that the characteristics of postpartum mother are at productive age as much as 95%, elementary education is 38.2% and 81% work as housewife. Result of univariate analysis of knowledge of mother good amount 71,4% and 57,1% mother have good attitude. From the results of bivariate analysis, good attitude toward traditional care has good knowledge of 83.3% based on FGD results obtained traditional care knowledge and attitude of cadre support to drink herbal medicine and some FGD participants believe by using traditional treatment can accelerate the puerperium and can give positive effect to postpartum recovery, but there are some who think traditional treatment is not recommended by health workers because it can have a negative impact. A strong reason for traditional treatments is the benefits for post-natal health recovery and for maintaining a healthy body for good activity..